Isolation and characterization of mer gene from mercury-resistant bacteria isolated frompolluted soil - Tan, Boon Khai. (Universiti Malaysia Sarawak (UNIMAS), 2009)
The anthropogenic activities have subsequently caused the arisen levels of mercury in the environment. Mercury pollution has caused severe problem to human due to its toxicity. It was discovered that the prokaryotes have developed the astonishing arrays of resistance system to defend against the polluted environments. Mercury resistance operon (mer operon) is one of the best understood biological systems to date for detoxifying organometallic or inorganic compounds, where the mercury reductase enzyme that encoded by merA gene, mediated the reduction of highly toxic ionic mercury, Hg2+ to relatively less toxic and volatile elemental mercury, Hgo. Through the study of mer operon, it can be utilized for bioremediation purpose, global recycling of mercury and also allow the study of horizontal gene transfer in the natural population. In this study, Klebsiella pneumoniae which had been isolated from Sungai Bera, Brunei Darussalam was screened for presence of merA gene using Polymerase Chain Reaction (PCR). The putative merA gene was cloned and sequenced --where the nucleotide sequence was revealed to show 77% similarity to the polysaccharide deacetylase domain protein of Klebsiella pneumoniae. Three additional mercury-resistant bacteria were successfully isolated from polluted soil sampled at Miri. The three isolates were subjected to 16S rONA sequencing and successfully identified as Bacillus pumilus, Bacillus thuringiensis and Bacillus aquimaris respectively.